Effects of Melaleuca cajuputi leaf extract on inhibition of seed germination and seedling growth of 12 weed species - Nakmee, Pattarawadee Sumthong; Chomtee, Boonorm; Juntaropakorn, Methee; Ngamprasit, Supranee (Agriculture and Natural Resources, 2023)
Importance of the work: Plant natural products are sources of numerous compoundswith antimicrobial, pesticide and allelopathic properties. Objectives: To test Melaleuca cajuputi leaf and powder extracts for their inhibitory effect on seed germination and seedling growth of 12 weed species. Materials & Methods: Petri dish and soil-based experiments were conducted to determine the efficacy of different percentages of the leaf powder and leaf extracts on the inhibition of weed seed germination. Results: Weed seed germination and seedling growth were inhibited by M. cajuputi leaf extract better than by branch extract in a Petri dish experiment, with inhibition better on broadleaf weeds than narrowleaf weeds. There was complete inhibition (100%) of the seed germination of the broadleaf weeds, Eclipta prostrata, Borreria alata, Tridax procumbens, Gomphrena celosioides, Amaranthus viridis and the narrowleaf weed, Chloris barbata with M. cajuputi leaf extract at amounts of 0.1−1.0 g dry weight. The major essential oil found in the M. cajuputi leaf extract was eugenol, with 0.015−0.2 M of eugenol inhibiting the seed germination and seedling growth of Achyranthes aspera. Main finding: In the soil-based experiment, there was 100% inhibition of weed seed germination using 6% leaf powder and 4−6% leaf extracts, which supported the potential use of M. cajuputi leaf extract as a natural herbicide for safe and sustainable agriculture.